THE IMPLEMENTATION OF GAME BASED LEARNING (GBL) METHOD TO IMPROVE EFL STUDENTS’ VOCABULARY MASTERY - Hidayah, Nurul; Sabarun, Sabarun; Widiastuty, Hesty (STKIP PGRI Situbondo, 2024)
This study was aimed to evaluate the implementation of Game-Based Learning (GBL) method to improve EFL students vocabulary mastery at SMPN Satu Atap 1 Katingan Hilir. The researcher chose class VII students totaling 23 as the subjects, and the informant was one English teacher. The research method employed was qualitative descriptive, enabling the researcher to gain in-depth insights into the effectiveness of GBL in improving the English vocabulary mastery of the students. Data was collected through observation, questionnaires, and interviews with English teachers involved in the teaching process. This data was used to evaluate the implementation of GBL in three phases: pre-teaching, while teaching, and post-teaching. The finding indicated that the implementation of Game-Based Learning (GBL) methods was effective in improving English vocabulary mastery EFL students at SMPN Satu Atap 1 Katingan Hilir. This indicated that a more interactive and enjoyable approach to learning addressed the previous weakness in English vocabulary mastery. The data analysis results demonstrated a substantial improvement in students' vocabulary mastery after they participated in learning sessions using the GBL method. Presenting learning material in the form of engaging games had the capability to improve students' learning interest, thus motivating them to actively participate and interact within the learning environment. Therefore, method GBL could be regarded as an effective alternative in designing enjoyable and efficient teaching strategies to improve EFL students' vocabulary mastery.